Morphological changes in joint anatomy in osteoarthritis: a cross-sectional study from Punjab, Pakistan - Asad, Ayesha; Younis, Aleena; Liaqat, Umar; Aman, Sadia; Shahzad, Naeem; Khan, Asma Niaz (Journal of Neonatal Surgery, 2025)
Background: Osteoarthritis (OA) is a leading cause of disability worldwide. Regional anatomical data on morphological joint changes in Pakistani populations are limited. We describe radiographic and MR-derived morphological changes in knee joints and identify demographic and anthropometric predictors of radiographic OA in a Punjab population. Methods: Cross-sectional study of 1,560 adult participants recruited from Benazir Bhutto Hospital, a tertiary hospital in Punjab (June 2022–December 2024). Inclusion: age ≥40 years; exclusion: inflammatory arthritis, prior knee joint replacement. Radiographs (weight-bearing AP) graded by Kellgren–Lawrence (KL). Subset (n=400) had knee MRI for cartilage thickness and osteophyte measurement. Primary outcome: radiographic OA (KL ≥2). Statistical tests: t-test/ANOVA, chi-square, Spearman correlation, multivariable logistic regression. Inter-rater reliability assessed by ICC. Results: Mean age 58.4 ± 9.7 years, 60.0% female (n=936). Radiographic OA (KL≥2) prevalence 46.8% (n=730). Mean medial joint space width (JSW) overall 3.6 ± 1.1 mm; OA group 2.4 ± 0.7 mm vs non-OA 4.6 ± 0.8 mm (p<0.001). MRI subset: mean cartilage thickness (medial femoral) 1.8 ± 0.4 mm in OA vs 2.9 ± 0.5 mm in non-OA (p<0.001). Multivariable logistic regression: age (per year) OR 1.06 (95% CI 1.04–1.07), female sex OR 1.45 (1.18–1.78), BMI (per kg/m²) OR 1.09 (1.07–1.11), JSW (per mm) OR 0.62 (0.57–0.67). Model AUC 0.82. Inter-rater ICC for JSW = 0.92 (95% CI 0.90–0.94). Conclusions: Morphological changes including reduced JSW and cartilage thinning strongly associate with radiographic OA. Age, female sex and BMI were independent predictors. Regional data will guide surgical planning and early interventional strategies in Punjab.